Altitudinal variation of phenological characters and initial growth under controlled conditions among Nothofagus pumilio populations from Center-West Chubut, Argentina - Mondino, Víctor A; Pastorino, Mario J; Gallo, Leonardo A (BOSQUE, 2019)
The genetic differentiation of six natural Argentine populations of lenga (Nothofagus pumilio) from the Center West of the Province of Chubut (42 ° 50 ‘S) distributed in an altitudinal range of 500 m (between 1,000 and 1,500 m a.s.l.) was studied by means of common garden greenhouse trials. Individual growth curves were fitted in one-year-old seedlings using the Boltzmann equation (non-linear regression). Inter-population variation was analyzed with ANOVA in several parameters of the fitted curves, indicative of the increase and the phenology of the growth process. Significant differences were shown between the upper populations and those of the intermediate and lower altitudinal level for the initiation and duration of the growth period, evidencing an ecotypic variation. Our results point out the relevance of considering the altitude of the seed origin in programs of ecological restoration or commercial plantation with lenga.